The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/bmjopen-2021-058523
|View full text |Cite
|
Sign up to set email alerts
|

Emotional impact on healthcare providers involved in medical assistance in dying (MAiD): a systematic review and qualitative meta-synthesis

Abstract: BackgroundMedical assistance in dying (MAiD) traverses challenging and emotionally overwhelming territories: healthcare providers (HCPs) across jurisdictions experience myriad of affective responses secondary to possible tensions between normative and interwoven values, such as sanctity of life, dignity in death and dying and duty to care.ObjectiveTo determine the emotional impact on HCPs involved in MAiD.MethodsInclusion restricted to English language qualitative research studies from four databases (OVID Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…However, the consequences of this mindset, that patients' right to autonomy takes precedence over a nurses' personal beliefs and values, was that nurses risked moral distress as a result. This finding is consistent with other research which concluded, nurses' face ethical dilemmas when dealing with AD and moral distress can result (Dholakia et al, 2022;Freeman et al, 2021;Patel et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the consequences of this mindset, that patients' right to autonomy takes precedence over a nurses' personal beliefs and values, was that nurses risked moral distress as a result. This finding is consistent with other research which concluded, nurses' face ethical dilemmas when dealing with AD and moral distress can result (Dholakia et al, 2022;Freeman et al, 2021;Patel et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this meta‐synthesis were consistent with other research that suggests health practitioners require clear policies and procedural guidelines for AD to feel confident and capable in having key discussions and providing quality service (Dholakia et al., 2022; Fujioka et al., 2018; Oliver et al., 2017). Nurses reported feeling afraid of the legal ramifications that could ensue yet also expressed their desire to be prepared for engaging with patients who expressed a desire for a hastened death.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…8 An individual’s professional values and level of engagement influence the emotional impact of MAiD. 9 Some of the stressors described by health care professionals include a feeling of isolation, a culture of secrecy, lack of support, few opportunities to talk about experiences, challenging relationships with colleagues who object and witnessing the grief of others. 10,11 Pharmacy students have reported concerns regarding the dispensing aspect of MAiD as well as issues they may encounter when practising in direct patient care.…”
Section: Introductionmentioning
confidence: 99%